Provision of critical care for the elderly in Europe: a retrospective comparison of national healthcare frameworks in intensive care units - Antonio Artigas; Nuno Catorze; Bernhard Wernly; Wojciech Szczeklik; Raimund Helbok; Pål Klepstad; Emmanuel Guerot; Tim Rahmel; Kelly Tiercelet; Louise Bell; Clare Bolger; Helder Filipe; et al. (BMJ Open, 2021)
Objectives In Europe, there is a distinction between two different healthcare organisation systems, the tax-based healthcare system (THS) and the social health insurance system (SHI). Our aim was to investigate whether the characteristics, treatment and mortality of older, critically ill patients in the intensive care unit (ICU) differed between THS and SHI.Setting ICUs in 16 European countries.Participants In total, 7817 critically ill older (≥80 years) patients were included in this study, 4941 in THS and 2876 in the SHI systems.Primary and secondary outcomes measures We chose generalised estimation equations with robust standard errors to produce population average adjusted OR (aOR). We adjusted for patient-specific variables, health economic data, including gross domestic product (GDP) and human development index (HDI), and treatment strategies.Results In SHI systems, there were higher rates of frail patients (Clinical Frailty Scale>4; 46% vs 41%; p<0.001), longer length of ICU stays (90±162 vs 72±134 hours; p<0.001) and increased levels of organ support. The ICU mortality (aOR 1.50, 95% CI 1.09 to 2.06; p=0.01) was consistently higher in the SHI; however, the 30-day mortality (aOR 0.89, 95% CI 0.66 to 1.21; p=0.47) was similar between THS and SHI. In a sensitivity analysis stratifying for the health economic data, the 30-day mortality was higher in SHI, in low GDP per capita (aOR 2.17, 95% CI 1.42 to 3.58) and low HDI (aOR 1.22, 95% CI 1.64 to 2.20) settings.Conclusions The 30-day mortality was similar in both systems. Patients in SHI were older, sicker and frailer at baseline, which could be interpreted as a sign for a more liberal admission policy in SHI. We believe that the observed trend towards ICU excess mortality in SHI results mainly from a more liberal admission policy and an increase in treatment limitations.Trial registration numbers NCT03134807 and NCT03370692.